2020
DOI: 10.18297/jri/vol4/iss1/58
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Common Respiratory Viruses During the COVID-19 Pandemic: Results From the Louisville COVID-19 Epidemiology Study

Abstract: Introduction: Social distancing has been utilized during the COVID-19 pandemic to reduce the spread of SARS-CoV-2, which is also expected to reduce the spread of common respiratory viruses. Methods: This retrospective, descriptive study assessed the rate of positivity of common respiratory viruses from commercially available respiratory pathogen panel, across a five-hospital health-system, during four-week periods within March to April of 2019 and 2020. Results: During the four-week period in 2019, the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This could be attributed to the current huge propaganda by media and health organizations about the importance of social distance to prevent dissemination of COV-19 between populations. In the same line, Brian et al, (2020) (6) , indicated that the social distancing efforts implemented in Louisville, Kentucky, may be associated with a decrease in incidence of common respiratory viruses. As well, Wong et al, (2020) (28) , reported that the More than one third of the studied employees in the current study agreed that taking the flu vaccine can reduce the risk of diseases of respiratory system (Table IV).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This could be attributed to the current huge propaganda by media and health organizations about the importance of social distance to prevent dissemination of COV-19 between populations. In the same line, Brian et al, (2020) (6) , indicated that the social distancing efforts implemented in Louisville, Kentucky, may be associated with a decrease in incidence of common respiratory viruses. As well, Wong et al, (2020) (28) , reported that the More than one third of the studied employees in the current study agreed that taking the flu vaccine can reduce the risk of diseases of respiratory system (Table IV).…”
Section: Discussionmentioning
confidence: 93%
“…There are other causes of microorganisms as fungi, and chemicals such as powder or dust that accidentally penetrate into the lungs which could also function as causative agents for RTIs (6,7) . Furthermore, many factors are involved in the large variation in the prevalence of transmission of respiratory tract infection including crowdedness, extreme temperature and dense air pollution, young and old age, preexisting health conditions,and improper personal hygiene (8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…5 This phenomenon is owed to individual and collective protective measures (masks, physical and social distancing, hygiene, etc. ), 6 , 7 which are factors that limit the transmission of SARS-CoV-2 and other respiratory viruses, including the flu. The decline in the number of analyses performed and the “blackout” of surveillance networks that suspended flu sampling could have a noteworthy impact on this equation.…”
mentioning
confidence: 99%